The role of the public policy clause in the Polish legal system on the example of cases concerning the conclusion and dissolution of marriage - Szczygieł, Adrianna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
The article aims to demonstrate the role of the public policy clause in the Polish legal system in the context of matrimonial relations, with a particular emphasis on the institution of the conclusion and dissolution of marriage. As a part of the discussion, the analysis reconstructs the essence of the public policy clause, while demonstrating the most important principles of family law and conflict-of-law rules concerning matrimonial matters. The author examines the relationship between the public policy clause and family law by emphasising differences in legal systems amongst different nations and specifying the authorised and prohibited implementation of the public policy clause regarding marriage conclusion and dissolution. It is also pointed out that child marriage, polygamy, and divorce through unilateral declaration of will, cannot be reconciled with Polish public order; and attention is drawn to the inadmissibility of establishing restrictions on the freedom to marry on the basis of racial, religious and social criteria. The author’s evaluation utilises case law, academic literature, and opinions from doctrinal representatives on this issue. The conclusion emphasises the significance of the public policy clause in preserving the consistency and uniformity of the Polish legal system as a tool to fight discrimination and gender inequality.